Body mass index mediates the association between sleep duration and academic performance: An evidence in Chinese adolescent students - Linni Gu; Rui Zhu; Donghua Tian (PLoS ONE, 2025)
Background Academic performance serves as a crucial indicator for evaluating adolescents’ educational outcomes in China, which prompting parents and schools to place significant emphasis on students’ academic achievements. However, the pursuit of excellent academic performance often leads to inadequate sleep duration, while the body mass index (BMI) is also disregarded when prioritizing academic achievement. This study aims to examine the association between sleep duration and academic performance and to explore the mediating role of body mass index (BMI) among adolescent students in rural and urban areas of China. Methods The study utilized baseline (2013–2014 academic year) and follow-up survey data (2014–2015 academic year) from the China Education Panel Study (CEPS). A total of 7,218 adolescent subjects aged between 12 and 14 were recruited using multi-stage random probability proportional to size sample (PPS) sampling, providing demographic, sleep duration, and body mass index (BMI) information. Descriptive analysis, Ordinary Least Square (OLS), and Product of Coefficients Approach were used to estimate the association and mediating role between sleep duration, BMI and academic performance. Results The sleep duration has significantly influenced the academic performance of adolescent students, (p < 0.01). A 10-minute increase in sleep duration was associated with a 6.3% decrease in academic performance for rural-urban students (β = -0.063, p < 0.01). Subgroup analyses further demonstrated that a 10-minute increase in sleep duration led to an 8.5% decrease in academic performance for rural adolescent students (β = -0.085, p < 0.01), while urban students experienced a 6.7% decrease under similar circumstances (β = -0.067, p < 0.05). Body mass index (BMI) negatively influenced students’ academic performance (β = -0.071, p < 0.01) and mediates the relationship between sleep duration and academic performance (β = 0.112, p < 0.001). Conclusions The sleep duration has negatively influenced rural-urban adolescent students’ academic performance in China, however, this influence was indirect when added the variable BMI into the model. The BMI played a mediating role in the relationship between sleep duration and academic performance.